Adequação proteica e desfechos em pacientes internados em unidade de terapia intensiva pediátrica - Crestani, Francielly (2018)
Introduction: Stress, in response to acute injury, is characterized by an increase in protein catabolism. Children, during hospitalization at the Pediatric Intensive Care Unit, accumulate substantial protein deficits that exert negative effects not only on their nutritional status, but also on clinical outcomes, such as longer hospitalization, higher risk of infections, and higher rates of mortality. Nutritional support during critical illness is essential to provide satisfactory amounts of energy and protein to mitigate the effects of catabolism, favoring the inflammatory response and preserving muscle mass. Objective: To evaluate the protein adequacy in the diet prescribed to patients hospitalized in a Pediatric Intensive Care Unit, and the relationship with the following outcomes: mortality, length of hospital stay, need for mechanical ventilation, and organ failure. Methods: Observational retrospective cohort study, performed through the review of medical records. Patients were admitted to the Pediatric Intensive Care Unit of a University Hospital in the South of Brazil, from January 1, 2015 to December 31, 2016. Patients aged 29 days and older who received enteral diet by tube and / or parenteral diet during the first ten days of admission to the unit. The variables collected included demographic data, severity score according to the Pediatric Index of Mortality 2, daily prescription of the diet volume to be offered to the patient, energy and protein value of the prescribed diet, length of hospital stay, need for mechanical ventilation and mortality. Protein target was considered to be 70% of the minimum recommended value for age by the American Society for Parenteral and Enteral Nutrition. The anthropometric evaluation was carried out from the measurement of weight and height. The body mass index for age (BMI/A) was the parameter chosen to evaluate the nutritional status of the patients. Continuous variables with normal distribution were compared using Student's t-test and continuous variables with asymmetric distribution were compared using the Mann-Whitney or Kruskal Wallis tests. Categorical variables were compared using the Chi-square or Relative Risk test. Differences were considered significant when p < 0.05. Results: A total of 352 patients were included in the study. The anthropometric evaluation through the BMI/A on admission found 15.9% of the patients malnutrition classification and 10.5% were classified as overweight. The protein target was reached by 37.5% of the patients and showed a significant association with organ dysfunctions, sepsis and mortality. Conclusion: Energy and protein prescription was inadequate in most of the evaluated patients. Protein inadequacy was associated with mortality in the sample studied. The implementation of nutritional support guidelines, focusing on the early initiation of enteral nutrition and adequate nutritional prescription, can optimize nutrient delivery and improve clinical outcomes in patients.